Virtual Reality and Beyond: The LabTEVE at UFPB in Brazil - Machado, Liliane S.; Moraes, Ronei M. (Journal on Interactive Systems, 2011)
Training systems, serious games, assessment methods, solution for VR and systems to support learning have been the focus of research at LabTEVE. Since 2000 several projects have been developed and evidenced the multidisciplinary context of the group researches. This paper presents some past and present activities developed in the LabTEVE at UFPB in Brazil and points to future trends.